Die Fresh Expression beweging en die Hervormde Kerk – "n nuwe manier van kerkwees? - Ungerer, André G. (2017)
The Fresh Expression movement is well-known in Great Britain and other Western countries like the USA, Australia and lately South Africa. During 2013, a task team launched two pilot courses in Cape Town and George that marked the beginning of Fresh Expressions in South Africa. The Nederduitsch Hervormde Kerk van Afrika (Netherdutch Reformed Church of Africa – NRCA) exposed 125 of her pastors to the Fresh Expression movement by means of the annual continuous theological training program during 2015. Three of the pastors underwent the ‘Train the Trainer’ course and are currently involved in the presentation of courses in the Pretoria region. The Fresh Expression movement hold the possibility for pioneers in church planting to reach the people who have no ties with the established church. By entering a certain context, faith communities are established by means of listening to the people in their context, serving them in a loving way, creating a community, evangelise and discipling them and starting their own unique way of worshipping. The new faith communities are not in competition with the established church but it is rather a question of a mixed economy where different types of church exists alongside each other in mutual respect and support. This study tries to establish basic criteria to distinguish a Fresh Expression from random missional outreaches by a congregation. Two potential Fresh Expressions in the NRCA were evaluated by the set criteria.
Keywords: Sociology and Ethics; Ancient Semitic and Classical Languages; Philosophy; Aspects of Religious Studies; Practical Theology; Ministers of Religion; Scholars; Philosophers; Theologians; Netherdutch Reformed Church; Theology